Just out of REACH: how REACH is failing to regulate nanomaterials and how it can be fixed, - Azoulay, David (Geneva, 2012)
"More than three years after the European Commission’s communication on the regulatory aspects of nanomaterials, numerous questions remain regarding the practical effectiveness of existing European Union law to manage nanomaterials. REACH, the primary EU regulation on chemicals, is assumed to be the regulatory cornerstone for addressing the health, safety and environmental risks of nanomaterials. In particular, REACH registration is described as the ideal tool to fill the problematic knowledge gap on nanomaterials. However, the limited information gathered in the first registration phase demonstrates that REACH is not living up to expectations for nanomaterials. The study identifies four areas in which REACH’s registration provisions fail to account for the specificities of nanomaterials."